Enabling pharmacogenomic clinical trials through sampling. (December 2010) - Warner, Amelia; Nelsen, Anita; Bhathena, Anahita; FitzGerald, Kevin; Gilardi, Sandra; Kelso, Ellen; Knoppers, Bartha; McLeod, Howard L; Nelson, Robert; Uyama, Yoshi; Weisman, Jennifer; Rudman, Allen
Discussion and output from the US FDA and the pharmaceutical industry from the Drug Information Association/FDA 5th Workshop in a series on pharmacogenomics entitled: 'Generating and Weighing Evidence in Drug Development and Regulatory Decision Making'. A major topic area at the 5th FDA/Industry Workshop on Pharmacogenomics, February 2–4, 2010 in Bethseda (MD, USA), was enabling pharmacogenomic clinical trials through collection of future use samples. The importance of the collection of samples with permission for future analyses was affirmed by both industry and the FDA. In addition, current barriers for the collection of such samples were detailed and possible solutions for overcoming barriers at sites, as well as globally within countries, were discussed. The importance of international concordance on collection of these samples was emphasized, and potential areas for industry to harmonize sample collection practices. A standalone workshop on issues related to sampling was determined to be a key step for solving issues related to future use sample collection during drug development.